Go tell it : how James Baldwin became a writer - Harris, Quartez (Little, Brown and Company, 2025)
"A boy who loves stories grows into a teenager who escapes into his writing and then a young man who plays his typewriter like a piano to show the fullness of Black life, in this lyrical picture book biography of James Baldwin, the celebrated novelist, essayist, playwright, poet, and activist"--